SYSTEM THINKING IN ADVANCING THE MODERATE AND INCLUSIVE ISLAMIC EDUCATION - Sumarni, Sri (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
In Islamic education, religious moderation is not merely to be taught or discussed but must be implemented in everyday life. As a system, the educational process cannot rely solely on one component but must involve all educational components in an integrated and synergistic manner. Therefore, this paper aims to offer insights into the importance of designing a comprehensive and systemic learning process based on the values of religious moderation. The approach used in this study is reconstructive and philosophical history. This study examines historical moments in Islamic civilization where Muslim scholars applied moderate values. Furthermore, the meaning of religious moderation must be fundamentally understood so that the values it contains can be easily implemented. Therefore, implementing religious moderation in Islamic education should begin with a paradigm shift regarding the nature of religious moderation itself. Once this paradigm is understood, the next stage leads to more practical aspects such as policy-making, programs, and the availability of human resources that fully support and serve as examples of religious moderation. The ideal system thinking approach should be carried out both vertically and horizontally. Vertically, the educational process begins from childhood through adulthood, encompassing education at the higher level. Meanwhile, horizontally, the quality of an individual's religious moderation is influenced by various factors, such as curriculum, approaches, educators, family backgrounds, the uniqueness of each learner, educator competencies, and so on.